10. Incidency And Fasciolosis Risk Factors In Cows In Pringsewu District, November 2019-January 2020 - S Valinata; J Susilo; B Pramono; T. Fadrial Karmil; Abdullah Hamzah; Fadli A Gani; M. Jalaluddin; Abdul Harris (Jurnal Medika Veterinaria, 2020)
Fasciolosis is a parasitic disease caused by infection with Fasciola sp. Fasciolosis has a big impact due to death, reduction in life weight, loss of labor, forced cattle to be removed, decreased milk production and medical costs. Predisposing factors to fasciolosis include age, maintenance system, season and species. The purpose of this study is to determine the Incidency of Fasciola sp. in beef cattle and identify risk factors that influence in the Pringsewu District unit. Samples were obtained from four sub-districts in Pringsewu District, with a total sample of 120. Samples were tested in the parasitology laboratory Lampung Veterinary Institute by sedimentation method. The results of these tests found 36 positive samples of Fasciola sp. (30%). Results of data processing, the factor of a semi-intensive maintenance system has a risk of 3.82 times compared to an intensive maintenance system (OR = 10.16; P-value = 0.007; 95% CI = 1.63 - 8.94). The absence of a mass deworming program has a 1.38-fold risk compared to those with a mass deworming program (OR = 0.63; P-value = 0.5; 95% CI = 0.63 - 3.01). Female gender has a risk of 1.33 times compared to male sex (OR = 0.22; P-value = 0.00003; 95% CI = 0.40 - 4.45). Adults have a 1.57-fold risk compared to young age (OR = 0.95; P-value = 0.018; 95% CI = 0.63 - 3.90). The conclusion of this study is the Incidency  of fasciolosis in Pringsewu Regency is 30% with the highest Incidency  occurring in Adiluwih sub-district by 50%. The intensive maintenance system has significant results in cases of fasciolosis. Mass deworming programs, gender and age have no significant effect on the incidence of fasciolosis. The combination of an intensive maintenance system with the provision of an appropriate anti-helminthes is the best combination to deal with cases of fasciolosis in Pringsewu District.